Inter-laboratory Comparison between Particle and Bacterial Filtration Efficiencies of Medical Face Masks in the COVID-19 Context - Axel Fouqueau; Jérémie Pourchez; Lara Leclerc; Aurélien Peyron; Yoann Montigaud; Paul Verhoeven; Tatiana Macé; Alexandre Bescond; Dominique Thomas; Augustin Charvet; Mathieu Ghijselings; Pauline Hars; et al. (Aerosol and Air Quality Research)
Abstract Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) transmission lead to the recommendation of mask wearing during the pandemic COVID-19. Bacterial filtration efficiency (BFE) measurements are used to measure the efficiency of medical face masks in preventing the spread of bioaerosols. Even though these measurements are simple, BFE testing still raise several scientific questions. This paper presents an inter-laboratory comparison between Bacterial Filtration Efficiency (BFE) and Particle Filtration Efficiency (PFE), in order to better understand and establish an overview of both ways for testing surgical masks. Filtration efficiency of six commercial surgical masks have been measured using such experimental methods, i.e., the BFE and the PFE using 3 µm particles initially developed for community face covering testing. The fractional filtration efficiencies have been measured and compared in order to explain the differences. Recommendations for improving associated EN14683:2019+AC standard are also proposed according to the results.